A brief history of pollution - Markham, Adam, 1948- (Routledge, 2019)
Originally published in 1994, this book links the distant past with the urgent problems of today, taking the reader on a literary and scientific tour of global pollution from pre-history to the post-industrial age. Ancient problems such as lead poisoning in Rome and water pollution in Mesopotamia provide the background to a discussion of modern catastrophes including the hole in the ozone layer, climate change and the global drinking water crisis. The book chronicles 800 years of pollution in London, charts the growth of environmental activism and spotlights the rise of the consumer society as the driving force behind today's malaise.